2017
DOI: 10.1063/1.5009087
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the tunneling magnetoresistance by using fluorinated graphene in graphene based magnetic junctions

Abstract: Spin polarized properties of fluorinated graphene as tunnel barrier with CrO2 as two HMF electrodes are studied using first principle methods based on density functional theory. Fluorinated graphene with different fluorine coverages is explored as tunnel barriers in magnetic tunnel junctions. Density functional computation for different fluorine coverages imply that with increase in fluorine coverages, there is increase in band gap (Eg) of graphene, Eg ∼ 3.466 e V was observed when graphene sheet is fluorine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Previous reports on MTJs using Gr spacer region are mostly limited to symmetric junctions in which both electrodes are the same material [15][16][17][18][19] . Our investigation includes symmetric junctions, both electrodes are Ni, and non-symmetric junctions, one is Ni and the other is Co and Gr monolayer (ML) is used as covalently bonded spacer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports on MTJs using Gr spacer region are mostly limited to symmetric junctions in which both electrodes are the same material [15][16][17][18][19] . Our investigation includes symmetric junctions, both electrodes are Ni, and non-symmetric junctions, one is Ni and the other is Co and Gr monolayer (ML) is used as covalently bonded spacer.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the electronic states of Gr at the Fermi level are mainly located at high symmetry K point in reciprocal space, 3 while only minority-spin states of Ni(111) and Co(111) exist at the K point [16][17][18] , which gives rise to a high TMR ratio.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] For the spintronic applications, there have been some studies on electronic transport properties based on CrO 2 electrode. [21][22][23][24][25][26] Meena and Choudhary [21][22][23][24][25] systemically investigated the spin transport properties for some magnetic tunnel junctions (MTJs) based on CrO 2 electrode and different barriers such as the graphene and the carbon nanotube, and large tunneling magnetoresistance (TMR) ratios were predicted. Leo et al 26 experimentally studied the TMR in the MTJ of CrO 2 /MgO/ CoFe (100), and revealed that the TMR sign can be reversed simply by subtle modications to the CrO 2 /MgO interface.…”
Section: Introductionmentioning
confidence: 99%